EpCAM Expression in Canine Malignant Mammary Tumors - Immunohistochemical Study - Rocha, Aline; Carvalheira, Júlio; Gartner, Maria de Fátima (Acta Scientiae Veterinariae, 2022)
Background: Epithelial cell adhesion molecule (EpCAM) is a glycoprotein responsible for multiple cellular functions that includes cell-to-cell adhesion and signal transduction. Studies in human breast cancer demonstrated that its overexpression has been linked to a more aggressive histological phenotype. However, in canine mammary tumors, its use is still scarce and its function, remains unknown. The main goal of the present study was to characterize the expression of EpCAM in canine mammary malignant tumors and associate its expression with clinicopathological features. Materials, Methods & Results: Forty-eight canine mammary samples were analyzed in the present study and went through the Hematoxylin-Eosin (HE) routine technique for histopathological and immunohistochemical analysis. EpCAM expression was evaluated considering the total immunolabelling (TI) which consists of the addition of 2 parameters: proportion score (PS) and intensity score (IS). Thirteen (27.1%) cases showed weak expression, 9 (18.7%) were characterized by a moderate expression and 27 (54.2%) were classified as intense. EpCAM overexpression was described in 36 (72.9%) primary tumors and in 5 lymph node metastases (71.4%). Immunoreactivity was, mainly, characterized by a staining in the lateral cell membrane of luminal epithelial cells, both in primary tumors and lymph node metastases. The statistical analysis was performed using the SPSS Statistics, version 24. Clinicopathological features, such as histological grade (P = 0.027), intravascular emboli (P = 0.004) and lymph node metastases (P = 0.016) demonstrated to be associated with a more aggressive histological type. Intravascular emboli and lymph node metastases were also linked to a higher histological grade. Discussion: EpCAM overexpression has been described in the literature both in canine mammary tumors and breast cancer. While the results in breast cancer could be ambiguous, depending on the tumor subtype, in the present study our findings demonstrated that overexpression was present in more than 50% of the total cases evaluated. In addition, immunoreactivity was also in accordance with the literature that describes membranous staining as the most prevalent pattern type. It was not possible to correlate overexpression with histological type and histological grade. However, those clinicopathological features are essential to evaluate tumor prognosis. For instance, our results demonstrated that histological type was statistically significant with histological grade (P = 0.027), intravascular emboli (P = 0.004) and lymph node metastases (P = 0.016). Additionally, the Nottingham system was statistically significant with intravascular emboli (P = 0.033) and lymph node metastases (P = 0.006). These findings have also been described in similar studies using canine mammary tissues in bitches. When it comes to pattern of expression in primary tumors and lymph nodes metastases, our findings described that neoplastic cell presented the same phenotype in these 2 different locations. In addition, loss of expression was also described in cluster cells within the subcapsular are which reflects the idea that the expression of EpCAM molecule changes according to time, which could be translated into the multistep process of metastases. Finally, it demonstrates that the development of neoplasia is not something static, but rather dynamic. Keywords: EpCAM, canine, bitches, mammary tumors, neoplasia, adhesion cell molecule, immunohistochemistry.